2018
DOI: 10.1074/jbc.ra117.000457
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of stimulator binding to a conserved pocket in the heme domain of soluble guanylyl cyclase

Abstract: Soluble guanylyl cyclase (sGC) is the receptor for nitric oxide and a highly soughtafter therapeutic target for the management of cardiovascular diseases. New compounds that stimulate sGC show clinical promise, but where these stimulator compounds bind and how they function remains unknown. Here, using a photolyzable diazirine derivative of a novel stimulator compound, IWP-051, and MS analysis, we localized drug binding to the β1 heme domain of sGC proteins from the hawkmoth Manduca sexta and from human. Coval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 50 publications
11
67
1
Order By: Relevance
“…We developed C‐terminal truncated versions of Ms sGC that lack both catalytic domains but retain the heme domain and respond to stimulator compounds, collectively referred to as Ms sGC‐NT proteins. We produce Ms sGC‐NT proteins in large quantity with fully loaded heme, allowing us to develop a model for domain arrangement, demonstrate linked‐equilibria binding between stimulator compounds and NO/CO, and localize stimulator compound binding to a site involving the β1 H‐NOX domain …”
Section: Introductionmentioning
confidence: 99%
“…We developed C‐terminal truncated versions of Ms sGC that lack both catalytic domains but retain the heme domain and respond to stimulator compounds, collectively referred to as Ms sGC‐NT proteins. We produce Ms sGC‐NT proteins in large quantity with fully loaded heme, allowing us to develop a model for domain arrangement, demonstrate linked‐equilibria binding between stimulator compounds and NO/CO, and localize stimulator compound binding to a site involving the β1 H‐NOX domain …”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling suggested binding to the supposed pseudo-symmetric site. However, earlier studies by the same group proposed binding of YC-1 to the catalytic domain [84], in contrast to the recent studies showing that these stimulators bind to the βHNOX domain [12]. Therefore, the exact binding site of these inhibitors remains elusive.…”
Section: Structural Determinants For Catalytic Activitymentioning
confidence: 99%
“…The remarkable opposite effects of the αCys595Ser (see section 4.1) and αCys595Tyr mutations on basal activity suggested that this residue is important for catalysis, despite not being part of the catalytic site. It was originally proposed that this residue is involved in YC-1 binding, but recent studies have shown that stimulators bind to the βHNOX sensor domain instead [12]. Instead, we proposed that αCys595 is part of a network of interfacial hydrogen bonds that promote an optimal orientation of both subunits for high catalytic activity [43].…”
Section: Structural Determinants For Catalytic Activitymentioning
confidence: 99%
See 2 more Smart Citations